2009
DOI: 10.1038/leu.2009.155
|View full text |Cite
|
Sign up to set email alerts
|

The TLR1/2 agonist PAM3CSK4 instructs commitment of human hematopoietic stem cells to a myeloid cell fate

Abstract: Toll-like receptors (TLRs) constitute a family of nonpolymorphic receptors that are devoted to pathogen recognition. In this work, we have explored the impact of TLR ligands (TLR-L) on human hematopoietic stem cells (HSCs) and hematopoietic progenitor cells (HPCs). We show that HSCs and HPCs have a comparable pattern of expression of TLR transcripts characterized by the predominance of TLR1, -2, -3, -4 and -6. In longterm cultures of HSCs, HPCs and stromal cells, most TLR-L profoundly inhibited B-cell developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 37 publications
5
107
0
Order By: Relevance
“…LPS also favors the retention of HSC in tissues and stimulates their local proliferation and their differentiation into DC (16). Human CD34 + progenitors also differentiate along the myeloid lineage upon TLR stimulation (18,20). Therefore, TLR signals represent an environmental factor that induces mobilization of HSC and generation of innate immune cells such as DC, providing a mean for a rapid replenishment of the innate immune system during infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS also favors the retention of HSC in tissues and stimulates their local proliferation and their differentiation into DC (16). Human CD34 + progenitors also differentiate along the myeloid lineage upon TLR stimulation (18,20). Therefore, TLR signals represent an environmental factor that induces mobilization of HSC and generation of innate immune cells such as DC, providing a mean for a rapid replenishment of the innate immune system during infection.…”
Section: Discussionmentioning
confidence: 99%
“…This impairment correlates with a decrease in Ag phagocytosis (14,15). Moreover, in recent years, TLR ligands have been shown to influence hematopoiesis, favoring the retention of hematopoietic progenitors in tissues and stimulating their local proliferation and differentiation into DC (16)(17)(18)(19)(20). This could provide a boost of fresh innate immune effector cells during infections that could sustain the adaptive immune responses against the pathogens.…”
mentioning
confidence: 99%
“…Mouse stem cells and early B-cell progenitors express and use TLR, a mechanism that facilitates their differentiation to the innate immune system (Nagai et al, 2006;Welner et al, 2008b;Welner et al, 2009). Recent work suggests that, as in mice, human primitive cells, including MLP, also express functional TLR (Kim et al, 2005;Sioud & Fløisand, 2007;De Luca et al, 2009;Doulatov et al, 2010). In shape with those findings, we have found that BM lymphoid progenitor-enriched fractions display TLR9 ( Figure 3) and their differentiation potentials bias toward NK and DC production upon TLR9 ligation (RP & EV, unpublished observations).…”
Section: The Early Steps In the Lymphoid Developmentmentioning
confidence: 99%
“…Since myelopoiesis is regulated through the balance between negative and positive signals, [19][20][21][22] we analyzed whether the generation of the putative NK/DC subset was preceded by modifications of both negative and positive regulators of myeloid development.…”
Section: Mb-il-15-dependent Reverse Signal Induces In Pb-nk Progenitomentioning
confidence: 99%
“…21 Thus, we used real-time PCR (RT-PCR) to investigate if the stimulation of mbIL-15-with its soluble ligand (IL-15Rα) could generate similar effects in PB-NKps. Analysis of Figure 2B shows that NKPs constitutively express the transcripts for GATA-1, PU.1 and that stimulation with the soluble IL-15Rα chain induced within three days a transient increase in the transcription rates of PU.1 (2-fold) and of GATA-1 (2-fold).…”
Section: Mb-il-15-dependent Reverse Signal Induces In Pb-nk Progenitomentioning
confidence: 99%